Property rights and conflict in Gomoa Nsuaem, Ghana’s central region - Emmanuel Ababio Ofosu-Mensah (Cogent Arts & Humanities, 2023)
This paper examines how contestation over property rights in Gomoa Nsuaem created conflict between the Twidan and Agona royal lineages in the community. The article employs archival, secondary and oral sources to critically clarify that Odikro Otenyi Kwaku of Gomoa Nsuaem reinvented tradition to satisfy his own parochial interests by selling off large tracts of Gomoa Nsuaem land popularly known as Otopaako Lands belonging to the Twidan Clan to Mankrado Kwaku Annor of the Agona clan as a result of his profligate and lecherous lifestyle. Hence the indigenous concept of land ownership beneficial for the entire clan was lost to the Twidan people.